Analisis Kebutuhan Pengembangan Bahan Ajar Digital IPAS Berbasis Kearifan Lokal Dilengkapi dengan Augmented Reality untuk Pembelajaran di Sekolah Dasar - Novita Riana Sari; Rokhmaniyah Rokhmaniyah; Dewi Indrapangastuti; Kartika Chrysti Suryandari; Moh. Salimi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study is motivated by the limited availability of contextual and interactive IPAS (Ilmu Pengetahuan Alam dan Sosial) teaching materials that integrate local wisdom and the latest technology in elementary school learning processes. The aim of this research is to analyze the initial needs for developing a digital IPAS teaching material based on local wisdom and enhanced with Augmented Reality to improve the quality of learning in elementary schools. This research employs a descriptive method. The subjects of the study include fifth-grade students, teachers, and the principal of SDN Kaliurip. The object of the research focuses on the need for interactive, contextual, and technology-based learning resources and media. Data collection techniques include observation, interviews, and questionnaires. The analysis results indicate that teachers still heavily rely on government-issued textbooks, which inadequately reflect local values and do not support interactive learning. Meanwhile, students show a high level of interest in digital teaching materials that can be accessed through electronic devices, offering visually engaging content and incorporating local cultural elements. Both teachers and students expressed the need for contextual digital teaching materials that are adaptive to learning characteristics and integrated with Augmented Reality technology to enhance student motivation, engagement, and understanding of the subject matter. The findings of this study serve as a critical foundation for developing digital IPAS teaching materials that support the Merdeka Curriculum while reinforcing students' cultural identity through innovative and meaningful learning.Penelitian ini dilatarbelakangi oleh terbatasnya bahan ajar IPAS yang bersifat kontekstual, interaktif, serta mengintegrasikan kearifan lokal dan teknologi terbaru dalam proses pembelajaran di sekolah dasar. Penelitian ini bertujuan untuk menganalisis kebutuhan awal pengembangan bahan ajar digital IPAS berbasis kearifan lokal dilengkapi dengan Augmented Reality untuk meningkatkan kualitas pembelajaran di sekolah dasar. Jenis penelitian ini adalah penelitian deskriptif. Subjek dari penelitian ini adalah guru, siswa kelas V, dan kepala sekolah SDN Kaliurip. Objek penelitian adalah kebutuhan terhadap sumber belajar dan media pembelajaran yang interaktif, kontekstual, dan berbasis teknologi. Teknik pengumpulan data meliputi observasi, wawancara, dan angket. Hasil analisis menunjukkan bahwa guru masih bergantung pada buku dari pemerintah yang kurang mencerminkan nilai-nilai lokal dan belum mendukung pembelajaran yang interaktif. Sementara itu, siswa menunjukkan ketertarikan tinggi terhadap bahan ajar digital yang dapat diakses melalui perangkat elektronik dan menampilkan visual yang menarik serta konten budaya lokal. Guru dan siswa sama-sama berharap adanya bahan ajar digital yang kontekstual, adaptif terhadap karakteristik belajar, dan dilengkapi teknologi Augmented Reality untuk meningkatkan motivasi, keterlibatan, serta pemahaman siswa terhadap materi. Hasil penelitian ini menjadi dasar penting dalam pengembangan bahan ajar digital IPAS yang mendukung Kurikulum Merdeka dan memperkuat identitas budaya siswa melalui pembelajaran yang inovatif dan bermakna.